SPARC Controls Melanoma Cell Plasticity through Rac1. - Salvatierra Colussi, Edgardo Enrique (2015)
Cell transition to a more aggressive mesenchymal-like phenotype is a hallmark of cancer progression that involves different steps and requires tightly regulated cell plasticity. SPARC (Secreted Protein Acidic and Rich in Cysteine) is a matricellular protein that promotes this transition in various malignant cell types, including melanoma cells. We found that suppression of SPARC expression in human melanoma cells compromised cell migration, adhesion, cytoskeleton structure, and cell size. These changes involved the Akt/mTOR pathway. Re-expression of SPARC or protein addition restored all the cell features. Suppression of SPARC expression was associated with increased Rac1-GTP levels and its membrane localization. Expression of the dominant negative mutant of Rac1 counteracted almost all the changes observed in SPARC-deficient cells. Overall, these data suggest that most of the SPARC-mediated effects occurred mainly through the blockade of Rac1 activity.